Permittivity and Backscattering Coefficient of Diesel Oil-Contaminated Soil at C Band (5.3 GHz). (28th January 2013) - Ahmadian, Nima; Hasan, Sayeh; Calla, Om Prakash Narayan
Abstract : Studying the behavior of soil contaminated by diesel requires the measurement and calculation of electrical parameters such as permittivity and backscattering coefficient. It is also necessary to study the physical parameters such as surface roughness. The intent of this paper is to present a broad and updated overview of the diesel oil contaminated soil, emphasizing permittivity and scattering coefficient that are involved in determining and detecting the rate at which and extent to which hydrocarbons contaminate the soil and environment. The measurement of permittivity and the calculations of backscattering coefficient values were made with different amounts of diesel oil contamination and different incident angles in 5° intervals ranging from 10° to 80° for both horizontal and vertical polarization at C band. The values of scattering coefficient for different look angles (25°, 30°, 35°, 40°, 45°, 50°, and 55°) were calculated and are suitable for comparison with data generated from other remote sensing platforms. Accurate electrical parameter measurements of soil contamination and recognition of their dependence on physical and chemical composition are interesting and can support using microwave remote sensing instruments to observe the earth.